1981
DOI: 10.1007/bf01912993
|View full text |Cite
|
Sign up to set email alerts
|

Double crystallization of biaxially oriented polypropylene

Abstract: The melting conditions of biaxially oriented polypropylene (BOPP) have a very strong effect on the courses of both non-isothermal and isothermal crystallization from the melt. It has been shown that the crystallization proceeds by two mechanisms. Depending on the melting conditions, both crystallization mechanisms can proceed individually or simultaneously (double crystallization). The high rate mechanism, occurring in non-isothermal crystallization at low undercooling and observed in isothermal crystallizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…It may be explained by the formation of a mixed polymorphic structure on one hand and, similarly to the observations with low-density polyethylene [13], by a fractional crystallization according to the chain regularity on the other hand.…”
Section: T Imentioning
confidence: 80%
“…It may be explained by the formation of a mixed polymorphic structure on one hand and, similarly to the observations with low-density polyethylene [13], by a fractional crystallization according to the chain regularity on the other hand.…”
Section: T Imentioning
confidence: 80%
“…3 shows the melting curves of polyethylene foils treated by the combined method, various numbers of temperature steps being applied. (More complicated cases of stepwise crystallization and heat treatment are discussed in other papers of our research group [7,8].…”
Section: Preparation Of Samples With Several Melting Peaksmentioning
confidence: 98%
“…We have found that the peaks of the melting curves are due to melting and recrystallization processes [7], and that the melting of high-pressure polyethylene faithfully reflects the thermal history of the sample. This phenomenon was given the name "thermal memory effect".…”
mentioning
confidence: 97%
See 2 more Smart Citations